Species inventory and density of gastropod in mangrove ecosystem at Tomini Bay Gorontalo - Rivani Usman; Munirah Tuli (Tomini Journal of Aquatic Science, 2022)
This study aimed to identify the inventory of gastropod species and Density at The Mangrove Ecosystem in Pentadu Timur Village, Tomini Bay, Gorontalo, from March to April 2022. Two observation stations were determined from purposive sampling, which was carried out in five transect lines and four quadrants measuring 1x1, while the gastropod samples were taken and then placed in a plastic bag for identification and documentation. In contrast, the density analysis was carried out descriptively by differentiating each species of Gastropod. The results showed that eight families and 11 species of gastropods were identified, namely; Monodonta labio, Cassidula aurisfelis, Littoraria sulcata, Nerita planospira, Chicoreus capucinus, Cerithium kobelti, Nassarius polygonatus, Cerithidea obtusa, Telescopium telescopium, and Tereblaria palustris. In both stations within the tourist area, two types of gastropod species experienced the highest and lowest densities for two months, namely Nassarius polygonatus, found at 20.4 ind/m² in march and 18.4 ind/m² in April, whereas the protected forest areas that species Telescopium found 14.2 ind/m² in march and 12.40 ind/m² in April